Molecular detection of Pythium insidiosum from soil in Thai agricultural areas - Nongnuch Vanittanakom (2018)
Pythium insidiosum is an aquatic fungus-like organism in the kingdom Stramenopila that causes pythiosis in both humans and animals. Human pythiosis occurs in ocular, localized granulomatous subcutaneous and systemic or vascular forms. Individuals whose occupations involve exposure to aquatic habitats have an elevated risk of contracting pythiosis. Previously, we reported the first successful isolation of Pythium insidiosum from aquatic environmental samples by culture including confirmation using molecular methods. In this study, we show that P. insidiosum inhabitats moist soil environments in agricultural areas. A total of 303 soil samples were collected from 25 irrigation sources in the areas nearby the recorded home addresses of pythiosis patients residing in northern provinces of Thailand. P. insidiosum DNA was identified directly from each soil extract by using a nested PCR assay and subsequent phylogenetic analysis of the ribosomal intragenic spacer region. P. insidiosum DNA could be detected from 16 of the 25 soil sources (64%). Conventional culture methods were also performed, however all samples exhibited negative culture results. We conclude that both irrigation water and soil are the natural reservoirs of P. insidiosum. In endemic areas, the exposure to these environmental reservoirs should be considered a risk factor for hosts susceptible to pythiosis. © 2013 Elsevier GmbH.